2003
DOI: 10.1103/physrevb.68.094409
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum spin dynamics in the fcc antiferromagnetNiS2with frustration

Abstract: The unusual coexistence of two antiferromagnetic ͑AF͒ long-range orderings ͑LRO͒ in single-crystal NiS 2 is investigated through measurements of inelastic neutron scattering, specific heat, uniform magnetic susceptibility, and resistivity. Neutron scattering intensity reveals a honeycomb pattern of the intensity distribution in reciprocal lattice space ͑continuous-line structure along the Brillouin zone boundaries͒ in the extended critical temperature region (T N1 ϭ39.3 KϽTϽ150 K) providing direct evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…2(a) inset]. As has been discussed above, various measurements such as the neutron scattering 37) and specific heat 23) measurements have proved that the phase below T N1 is not spin glass but has the AF long-range order. We have clarified for the first time the isotropic character of the hysteresis in the NAF-phase.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…2(a) inset]. As has been discussed above, various measurements such as the neutron scattering 37) and specific heat 23) measurements have proved that the phase below T N1 is not spin glass but has the AF long-range order. We have clarified for the first time the isotropic character of the hysteresis in the NAF-phase.…”
mentioning
confidence: 89%
“…Previously, the surface effect was discussed to explain the sample dependence of the susceptibility observed in the paramagnetic phase (PM-phase) above T N1 ¼ 38 K. 34) It has been reported that the susceptibility χ in the PM-phase increases with increasing surface area 21) and strongly depends on the magnetic field 0 H. 23) To make a detailed comparison, we summarized the reported values of the magnetic susceptibility at 50 K, 21,23,33) χ(50 K), for NiS 2 in addition to our results (S-1) in Table I. Indeed, the samples used in the literature that claims the surface contribution show relatively large susceptibility values as well as strong field dependence.…”
mentioning
confidence: 99%
“…Therefore, magnetic quasielastic scattering in the paramagnetic phases was intensively studied by neutron scattering in spinel, pyrochlore, kagome, triangular systems, and so on. As a result, characteristic spatial correlations of spins were found, such as a small six-spin cluster [3][4][5][6][7][8], a large six-spin cluster [9], a seven-spin cluster [10], spin ice [11,12], and short-range order with propagation vector(s) [13,14].…”
mentioning
confidence: 99%
“…In this paper, we focus on the antiferromagnetic (AF) χ-SDW metals and insulators with ℓ S ℓ = 0 in materials and models with strong electron correlation and magnetic frustration. They have been discovered in charge transfer insulators NiS 2 [8][9][10][11], metallic γ-FeMn alloys [12][13][14][15] and related materials where the magnetic moments reside on the frustrated face-centered-cubic lattice. Neutron scattering observed noncoplanar AF order with 4-sublattices and 3-ordering wavevectors.…”
mentioning
confidence: 99%
“…On the theoretical side, it has been shown that frustrated Heisenberg two-spin exchange interactions are insufficient to produce the AF χ-SDW order; additional 4-spin exchange interactions are necessary for such a noncoplanar SDW to emerge from the many degenerate magnetic states [11,[16][17][18]. In addition, weak-coupling approaches such as nesting based models [19] and band structure (LDA) and LDA+U calculations [11,20,21] have been performed to study the complex magnetic order in these materials. While a microscopic theory for the χ-SDW order is currently lacking, it is believed that both strong correlation and geometric frustration play vital roles in its origin.…”
mentioning
confidence: 99%